MicroRNA Regulation of Brown Adipogenesis and Thermogenic Energy Expenditure - Shamsi, Farnaz; Zhang, Hongbin; Tseng, Yu-Hua (Frontiers in Endocrinology, 2017)
Obesity, diabetes, and associated metabolic diseases have become global epidemics. Obesity results from excess accumulation of white fat, while brown and its related beige fat function to dissipate energy as heat, thus counteracting obesity and its related metabolic disorders. Understanding the regulatory mechanisms for both white and brown adipogenesis provides new insights for prevention and treatment of these metabolic diseases. In addition to traditional gene transcription and translation, microRNA (miRNA) represents a new layer of regulatory mechanism in many biological processes and has attracted a great deal of research interests in exploring their roles in physiological and pathophysiological conditions. This review focuses on the recent advances of regulating brown adipogenesis and energy metabolism by miRNAs, aiming to delineate the regulatory principles of miRNAs on this unique aspect of energy homeostasis.